2012
DOI: 10.1089/jir.2011.0109
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-33 Levels Are Associated with Liver Damage in Patients with Chronic Hepatitis B

Abstract: This aim of this study was to assess the potential role of IL-33 in the pathogenic process of chronic hepatitis B (CHB). The levels of serum IL-33 and soluble ST2 (sST2) in CHB patients and healthy controls (HC) were determined using enzyme-linked-immunosorbent serologic assay, and the Th1 (IFN-γ, TNF-α, IL-2) and Th2 (IL-4, IL-6, IL-10) cytokines by cytometric bead array. It was found that the levels of serum IL-33 in CHB patients were significantly higher than that of HC at the base line, but decreased after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 30 publications
(6 reference statements)
4
40
0
Order By: Relevance
“…Results of IHC staining for IL‐33 were similar to the findings of previous reports . IL‐33 staining was concentrated in the nuclei of vascular endothelial cells and sinusoidal endothelial cells in areas of inflammation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Results of IHC staining for IL‐33 were similar to the findings of previous reports . IL‐33 staining was concentrated in the nuclei of vascular endothelial cells and sinusoidal endothelial cells in areas of inflammation.…”
Section: Discussionsupporting
confidence: 87%
“…IL‐33 has been reported to correlate with liver injury in patients with primary biliary cirrhosis (PBC) . Notably, serum levels of IL‐33 were closely associated with the degree of liver injury in patients with hepatitis B virus (HBV) infection . Moreover, the evaluation of dynamic changes in sST2 levels in HBV acute‐on‐chronic liver failure showed that serum sST2 levels increased over time in patients who died during follow‐up but decreased in those who survived.…”
mentioning
confidence: 99%
“…Such an understanding is supported by the markedly elevated serum levels of TGF-␤1 and IL-31 in ACLF patients and by the strong correlation between them in our study. Furthermore, we also found the serum levels of IL-17, IL-22, IL-33, and IL-35 were significantly increased in ACLF patients compared to the NC group, and serum levels of TGF-␤1 and IL-31 were all positively correlated with IL-17, IL-22, and IL-33, which have all been demonstrated to be proinflammatory cytokines in HBV-related diseases (23,32,33). Also, we found that serum levels of IL-9, IL-10, and IL-35 were elevated in the nonsurvivor ACLF patients.…”
Section: Discussionmentioning
confidence: 54%
“…In patients with chronic hepatitis B, the serum level of IL-33 was significantly higher than in healthy people. The level of cytokine decreased in serum in response to a 12-week treatment with adefovir dipivoxil (41). During hepatitis C, the serum level of IL-33 correlated with transaminase levels and was higher in patients with chronic hepatitis than in patients who spontaneously recovered or in healthy people (42).…”
Section: The Il-33/st2 Pathway and Viral Infectionsmentioning
confidence: 96%